2019
DOI: 10.1016/j.adolescence.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

E‐cigarette use and sleep‐related complaints among youth

Abstract: Introduction: E-cigarette use is highly prevalent among adolescents. However, little research has examined the relationship between e-cigarette use and sleep-related complaints in this population. The objective of this study was to assess whether exclusive e-cigarette, exclusive combusted cigarette, and dual-product use are associated with sleep-related complaints among adolescents. Methods: Participants were 9,588 U.S. adolescents from the Population Assessment of Tobacco and Health Study, a nationally repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Specifically, we observed a significant interaction between e‐cigarette and combustible cigarette frequency in predicting global sleep quality, such that high CPD was associated with worse global sleep quality scores, whereas high e‐cigarette use was not. This finding echoes previous research reporting that dual users were most at‐risk for worse overall sleep quality, 29,30 but high use of different cigarette types appears to have differential effects.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Specifically, we observed a significant interaction between e‐cigarette and combustible cigarette frequency in predicting global sleep quality, such that high CPD was associated with worse global sleep quality scores, whereas high e‐cigarette use was not. This finding echoes previous research reporting that dual users were most at‐risk for worse overall sleep quality, 29,30 but high use of different cigarette types appears to have differential effects.…”
Section: Discussionsupporting
confidence: 83%
“…A key assumption is that nicotine disrupts the sleep/wake cycle through its stimulating properties; thus, there is a need to understand the nuanced association between frequency of nicotine intake and sleep health. Second, many studies examining sleep have relied on either a single sleep question 29,31 or used a global metric of sleep quality, such as the total score of the Pittsburgh Sleep Quality Index 32 . Despite the strengths of the PSQI global sleep quality index, it does not provide an understanding of unique facets of subjective sleep quality, including next‐day tiredness and nightly awakenings 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of marijuana and tobacco was significantly associated with greater sleep problems among adolescents (Zhabenko et al, 2016). In addition, teens with more consumption of alcohol experienced later sleep schedules and more sleep on weekends compared with weekdays (Singleton & Wolfson, 2009), while those who used e-cigarettes tended to have shorter total sleep time on weekends (Dunbar et al, 2017) and had increased complaints related to sleep (e.g., bad dreams, sleeping restlessly, or falling asleep during the daytime; Riehm et al, 2019) compared to the nonusers. The association between sleep and substance use has been an interest among researchers for a long period of time, but relatively limited studies exist for adolescents.…”
mentioning
confidence: 99%
“…Only one study did not find a difference in sleep duration or quality in e-cigarette users; however, this study design had concerning limitations using unvalidated methods for assessing sleep [5]. The remaining nine articles had findings supportive of a relationship between e-cigarette use and decreased sleep quality including sleep duration, onset, latency or regularity [6][7][8][9][10][11][12][13][14]. In summary, although the articles all had unique limitations from study design to generalizability of findings, the vast majority of the articles concluded that e-cigarette or dual use leads to alterations in sleep that need further investigation.…”
Section: Introductionmentioning
confidence: 92%